Retinal Development in a Precocial Bird Species, the Quail (Coturnix coturnix, Linnaeus 1758) - Guadalupe Álvarez-Hernán; José Antonio de Mera-Rodríguez; Violeta Calle-Guisado; Gervasio Martín-Partido; Joaquín Rodríguez-León; Javier Francisco-Morcillo (Cells, 2023)
The quail (Coturnix coturnix, Linnaeus 1758), a notable model used in developmental biology, is a precocial bird species in which the processes of retinal cell differentiation and retinal histogenesis have been poorly studied. The purpose of the present research is to examine the retinogenesis in this bird species immunohistochemically and compare the results with those from previous studies in precocial and altricial birds. We found that the first PCNA-negative nuclei are detected at Stage (St) 21 in the vitreal region of the neuroblastic layer, coinciding topographically with the first αTubAc-/Tuj1-/Isl1-immunoreactive differentiating ganglion cells. At St28, the first Prox1-immunoreactive nuclei can be distinguished in the vitreal side of the neuroblastic layer (NbL), but also the first visinin-immunoreactive photoreceptors in the scleral surface. The inner plexiform layer (IPL) emerges at St32, and the outer plexiform layer (OPL) becomes visible at St35—the stage in which the first GS-immunoreactive Müller cells are distinguishable. Newly hatched animals show a well-developed stratified retina in which the PCNA-and pHisH3-immunoreactivies are absent. Therefore, retinal cell differentiation in the quail progresses in the stereotyped order conserved among vertebrates, in which ganglion cells initially appear and are followed by amacrine cells, horizontal cells, and photoreceptors. Müller glia are one of the last cell types to be born. Plexiform layers emerge following a vitreal-to-scleral gradient. Finally, our results suggest that there are no significant differences in the timing of different events involved in retinal maturation between the quail and the chicken, but the same events are delayed in an altricial bird species.